2012
DOI: 10.1002/chem.201202869
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Transfer in SAM‐Mediated Enzymatic Radical Reactions

Abstract: S-adenosylmethionine (SAM) plays an essential role in a variety of enzyme-mediated radical reactions. One-electron reduction of SAM is currently believed to generate the C5'-desoxyadenosyl radical, which subsequently abstracts a hydrogen atom from the actual substrate in a catalytic or a non-catalytic fashion. Using a combination of theoretical and experimental bond dissociation energy (BDE) data, the energetics of these radical processes have now been quantified. SAM-derived radicals are found to react with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 56 publications
(136 reference statements)
0
36
0
Order By: Relevance
“…97d Computational studies have provided further thermodynamic rationale for invoking intermediary amino acid radicals, as this would provide an SPL mechanism that avoids any strongly endothermic or exothermic steps. 478,479 …”
Section: Using Radical Sam Chemistry To Cleave C–x (X = C N P) Bondsmentioning
confidence: 99%
“…97d Computational studies have provided further thermodynamic rationale for invoking intermediary amino acid radicals, as this would provide an SPL mechanism that avoids any strongly endothermic or exothermic steps. 478,479 …”
Section: Using Radical Sam Chemistry To Cleave C–x (X = C N P) Bondsmentioning
confidence: 99%
“…[1][2][3][4] Together with BDE data for other dipeptide radicals this was taken to reflect steric interactions between the C a substituents and the amide groups present on the N-and C-terminal side of the central amino acid radicals. …”
Section: Introductionmentioning
confidence: 99%
“…While this manuscript was under review, Hioe and Zipse reported theoretical data of potential thermochemical profiles. 19 They also suggest that the SPL enzyme can circumvent the endothermic formation of the adenosyl radical when the radical chain reaction is propagated by an intermediate tyrosyl radical. Although formation of the Tyr98 radical is based on our data very likely, this conclusion needs further substantiation particularly based on EPR spectroscopic data.…”
mentioning
confidence: 99%